(untitled) (Bangladesh Agronomy Journal, 2022)
Soil salinity is becoming an alarming issue in crop production and increasing trend with a disastrous effect in near future. An experiment was conducted following completely randomized design to investigate the responses of zinc (Zn) priming (0.5 and 1.0 mM ZnSO4· 7H2O) upon exposure to different salt concentrations (50, 100, and 150 mM NaCl) in mitigating salt-induced damages in soybean (Glycine max L.). Results evidenced that shoot and root length, stem diameter, number of branches, number of leaves, and shoot and root biomass was reduced in a dose-dependent manner compared to control seedling. In a contrary, Zn priming resulted in the improvement of the parameters, particularly at a lower dose of salt. Moreover, leaf reduced relative water content and proline content were revived in primed seed in comparison with non-primed stressed plants. These triggers soybean plants’ tolerance to salt stress. It was concluded that priming seeds with lower concentration of Zn (0.5 mM) could alleviate the salt stress through improving plant growth characteristics, relative water content while decreasing proline content. Bangladesh Agron. J. 2022, 25(1): 47-56